2015
DOI: 10.1002/psp.1932
|View full text |Cite
|
Sign up to set email alerts
|

Escaping Homelands with Limited Employment and Tertiary Education Opportunities: Outbound Student Mobility from Post-Soviet Countries

Abstract: Despite the phenomenal growth in the numbers of international students, research focusing on mobile students from post‐Soviet countries is still extremely scarce. This paper offers an empirical investigation and theorisation of student mobility from post‐Soviet countries to contribute to the growing body of research on the topic of international student mobility that so far has largely focused on English‐speaking destination countries. Using secondary numeric data, I provide a snapshot of undergraduate student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 62 publications
1
38
0
Order By: Relevance
“…The dual education system that was accepted there, allows to provide a high level of proficiency of graduates of institutions of professional education, and creates conditions for successful social adaptation of youth (Falyakhov, 2015). All these factors as well as one of the highest level of public financing of the higher education in the world, caused very rapid growth of percent of gifted students who decided to continue their training in Germany, but not in domestic higher education institutions (Chankseliani, 2016;Habibov & Cheung, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The dual education system that was accepted there, allows to provide a high level of proficiency of graduates of institutions of professional education, and creates conditions for successful social adaptation of youth (Falyakhov, 2015). All these factors as well as one of the highest level of public financing of the higher education in the world, caused very rapid growth of percent of gifted students who decided to continue their training in Germany, but not in domestic higher education institutions (Chankseliani, 2016;Habibov & Cheung, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this volume, both Jumakulov and Ashirbekov (2016) and Pusztai and colleagues (2016) note that a substantial proportion of inbound student mobility is attributable to students from neighboring nations, and at least some of these inbound students from neighboring nations are ethnic Kazakhs and ethnic Hungarians, respectively. "Horizontal mobility" (Rivza & Teichler, 2007), defined as the educationrelated movement of students between national education systems of similar quality and sometimes between neighboring nations, has been documented in prior research on former Soviet and Eastern bloc nations (e.g., Chankseliani, 2015;Heyneman & Skinner, 2014;Rivza & Teichler, 2007). Chankseliani (2015) found that three of the five most popular destination countries for mobile students in the former Soviet region were Russia, Kyrgyzstan, and Kazakhstan.…”
Section: Mobility Is a Predominant Internationalization Activitymentioning
confidence: 94%
“…"Horizontal mobility" (Rivza & Teichler, 2007), defined as the educationrelated movement of students between national education systems of similar quality and sometimes between neighboring nations, has been documented in prior research on former Soviet and Eastern bloc nations (e.g., Chankseliani, 2015;Heyneman & Skinner, 2014;Rivza & Teichler, 2007). Chankseliani (2015) found that three of the five most popular destination countries for mobile students in the former Soviet region were Russia, Kyrgyzstan, and Kazakhstan. Heyneman and Skinner (2014) found that, with the exception of the Baltic states, one out of four internationally mobile students from former Soviet nations studies in Russia.…”
Section: Mobility Is a Predominant Internationalization Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…13 Third, according to Chankseliani (2016), Georgia has the fourth highest outbound mobility ratios of 14 post-Soviet states, with the most popular destination countries being (in order) Russia, Germany, Armenia, the United States, and France. However, after speaking with various government officials, it is not clear if student mobility figures are accurate, as government offices have reported that there is no unified mechanism for capturing student and faculty mobility data.…”
mentioning
confidence: 99%